Association of Geography and Access to Health Care Providers With Long‐Term Prescription Opioid Use in Medicare Patients With Severe Osteoarthritis: A Cohort Study. Issue 5 (2nd April 2019) - Desai, Rishi J.; Jin, Yinzhu; Franklin, Patricia D.; Lee, Yvonne C.; Bateman, Brian T.; Lii, Joyce; Solomon, Daniel H.; Katz, Jeffrey N.; Kim, Seoyoung C.
Abstract : Objective: To evaluate the variation in long‐term opioid use in osteoarthritis (OA) patients according to geography and health care access. Methods: We designed an observational cohort study among OA patients undergoing total joint replacement (TJR) in the Medicare program (2010 through 2014). The independent variables of interest were the state of residence and health care access, which was quantified at the primary care service area (PCSA) level as categories of number of practicing primary care providers (PCPs) and categories of rheumatologists per 1, 000 Medicare beneficiaries. The percentage of OA patients taking long‐term opioids (≥90 days in the 360‐day period immediately preceding TJR) within each PCSA was the outcome variable in a multilevel, generalized linear regression model, adjusting for case‐mix at the PCSA level and for policies, including rigor of prescription drug monitoring programs and legalized medical marijuana, at the state level. Results: A total of 358, 121 patients with advanced OA, with a mean age of 74 years, were included from 4, 080 PCSAs. The unadjusted mean percentage of long‐term opioid users varied widely across states, ranging from 8.9% (Minnesota) to 26.4% (Alabama), and this variation persisted in the adjusted models. Access to PCPs was only modestly associated with rates of long‐term opioid use between PCSAs with highest (>8.6) versus lowest (<3.6) concentration of PCPs (adjusted mean difference 1.4% [95% confidence interval 0.8%, 2.0%]), while access to rheumatologists was not associated with long‐term opioid use. Conclusion: We note a substantial statewide variation in rates of long‐term treatment with opioids in OA, which is not fully explained by the differences in access to health care providers, varying case‐mix, or state‐level policies.